2021
DOI: 10.1002/srin.202100507
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art in Control of Inclusions and Microalloying Elements in Tire Cord Steel and Saw Wire Steel

Abstract: The extremely thin diameter of steel tire cord wire and steel saw wire are about 80 and 50 μm, respectively. It is supposed that this kind of ultrafine steel wire is easy to break due to large and hard nonmetallic inclusions in the steel during the drawing and standing process. This paper reviews the research advances on inclusion and microalloying elements control in tire cord steel and saw wire steel in the past 20 years. Including: 1) calculation of thermodynamics of inclusion formation in quaternary system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Scholars have discovered that adding an appropriate amount of rare earth elements (La and Ce) to steel can improve the corrosion resistance and wear resistance of structural steel, as well as extend its life cycle. Existing research can fully explain the benefits of incorporating rare earth elements [1][2][3][4][5][6][7]. However, recent research has revealed that the alloying process of rare earth elements, as well as the problem of nozzle clogging in rare earth steel, are still significant issues that impede the efficient utilization of rare earth elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have discovered that adding an appropriate amount of rare earth elements (La and Ce) to steel can improve the corrosion resistance and wear resistance of structural steel, as well as extend its life cycle. Existing research can fully explain the benefits of incorporating rare earth elements [1][2][3][4][5][6][7]. However, recent research has revealed that the alloying process of rare earth elements, as well as the problem of nozzle clogging in rare earth steel, are still significant issues that impede the efficient utilization of rare earth elements.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction coefficient (1873K)[4] . capacity of Al 2 O 3 , the activity of Al 2 O 3 at different basicity was calculated, as shown in Figure11.…”
mentioning
confidence: 99%
“…Summarily, Al 2 O 3 has a detrimental effect on the deformability of inclusions in tire cord steel and needs to be strictly controlled during the refining process. From Chen's review, he concluded that how the size of typical inclusion MnO-SiO 2 -Al 2 O 3 affects the wire drawing process was not clear [23]. Niu [20] studied that the variation of Al 2 O 3 content in MnO-SiO 2 -Al 2 O 3 inclusions directly affects the plastic deformability of MnO-SiO 2 inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In general, inclusions are undesired because they can decrease the production capacity of the steelshops or negatively influence the properties of steel in service. [7][8][9][10][11][12][13][14][15][16] In this context, the availability of accurate methods to characterize steel inclusions is of paramount importance to acquire knowledge about their generation and to develop ways to control them.…”
Section: Introductionmentioning
confidence: 99%